Numerical investigation on the cooling of electronics components with synthetic multi-jets and non-sinusoidal bi-periodic forcing functions. (February 2020) - Benayad, Zouaoui; Laouedj, Samir; Filali, Abdelkader
Abstract: Recently, the cooling process for electronics components has attracted many researchers and several techniques for improving the cooling efficiency and heat transfer rate have been demonstrated. One of the best efficient techniques is the introduction of a synthetic jet and the modification of heating surface. In the present study, the form of heating surface and the signal of the diaphragm has been modified to improve the synthetic jet. These modifications are novel and have been applied for the first time with very good thermal enhancement efficiency for microchannels with synthetic jets applications. This study allowed us to make a quantitative comparison between a basic case with a periodic signal and modified case with bi-periodic signal with two cavities having a slope of 3°, 60 percent obstruction orifices and 10 mu m of undulation heated wall. The unsteady flow and heat transfer for the two-dimensional synthetic jet are solved using ANSYS fluent code and k- ω (SST) model is selected to account for fluid turbulence. Obtained results showed an increase of Nusselt number by about 51% for the modified case compared with the basic case.